MATERIAL DEPOSITION ON ALUMINIUM BY ELECTRICAL DISCHARGE COATING (EDC) WITH A TUNGSTEN POWDER SUSPENSION - Liew, P.J.; Yap, C.Y.; Nurlishafiqa, Z.; Othman, I.S.; Chang, S.Y.; Toibah, A.R.; Wang, J. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In this research, material deposition on an aluminium mould and die material was carried out via electrical discharge coating (EDC) with a tungsten powder suspension. The effects of EDC parameters, such as peak current (IP), pulse-on time (TON) and discharge voltage (V), on the weight percentage of deposited elements and micro-hardness and surface topography of aluminium were experimentally investigated. Results showed that five elements, including carbon, aluminium, tungsten, oxygen and copper, were deposited on the aluminium surface. The amount of deposited materials was strongly affected by IP, TON and V. Bulk deposition and globules formed on the material surface after EDC, and the micro-hardness of the material increased twofold compared with that of the base aluminium under the conditions of IP = 3 A, TON = 150 µs and V = 40 V.